Silicone rubber-based composite electrolyte and preparation method and application thereof

CN122907720APending Publication Date: 2026-10-13BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610974634.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]为克服现有硅橡胶固态电解质离子电导率有限、机械抗穿刺性能不足以及高电流密度下循环稳定性不佳的问题,本发明提供一种硅橡胶基复合电解质及其制备方法与应用

Benefits of technology

(1)本发明通过巯基-烯点击反应将极性官能团引入硅橡胶链段,提高硅橡胶对锂盐的解离和锂离子的传导能力,同时保持硅橡胶高弹性和良好界面贴合性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application relates to the technical field of battery, in particular to a kind of silicon rubber-based composite electrolyte and its preparation method and application.The electrolyte includes silicon rubber, modified small molecule, photoinitiator, crosslinking agent, doped ion hydroxyapatite and lithium salt.Modified silicon rubber matrix has the advantages of smooth surface, good flexibility, strong elastic recovery ability, high thermal stability and low glass transition temperature, etc.The introduced doped ion hydroxyapatite forms continuous ion transport network with nanowires or is uniformly dispersed in the silicon rubber matrix, which can promote the migration of lithium ions, enhance the dissociation of lithium salt, improve the stability of lithium negative electrode interface, and synergistically improve the mechanical strength, thermal stability and flame retardant safety of the electrolyte.The electrolyte has good flexibility, elasticity, interface adhesion and film-forming property.Application of the electrolyte in batteries can improve the ion transport performance, electrochemical stability, high voltage range, flame retardancy and thermal stability of the batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a silicone rubber-based composite electrolyte, its preparation method, and its application. Background Technology

[0002] With the development of high-energy-density energy storage devices, lithium metal batteries have attracted widespread attention due to their high theoretical specific capacity and low electrochemical potential. However, traditional liquid electrolytes suffer from problems such as flammability, leakage, and difficulty in suppressing the continuous growth of lithium dendrites, which limit the safety and cycle life of lithium metal batteries. Solid-state electrolytes can improve these problems to some extent and are an important component of next-generation high-safety lithium metal batteries.

[0003] Polymer solid electrolytes possess advantages such as high flexibility, good processability, and excellent interfacial adhesion. However, most polymer systems exhibit low room-temperature ionic conductivity, and it is difficult to balance mechanical strength and flexibility. Silicone rubber, with its low glass transition temperature, high elasticity, and good thermal stability, is suitable for constructing flexible solid electrolytes. However, single silicone rubber systems have weak polarity, limited lithium salt dissociation ability, and insufficient puncture resistance. Under high current density and long cycling conditions, problems such as increased interfacial impedance and lithium dendrite puncture may still occur.

[0004] Inorganic active fillers can improve the mechanical properties, thermal stability, and ion transport capacity of polymer electrolytes. Hydroxyapatite possesses a stable inorganic crystal framework and abundant surface sites, providing continuous lithium-ion migration channels. Further constructing it into a nanowire fiber network and compositing it with a flexible silicone rubber matrix is ​​expected to simultaneously improve the ionic conductivity, puncture strength, interfacial stability, and electrochemical window of silicone rubber electrolytes. Therefore, developing a silicone rubber-based composite electrolyte with a continuous structure, compatible interfaces, and easy preparation is of great significance. Summary of the Invention

[0005] To overcome the limitations of existing silicone rubber solid electrolytes, such as limited ionic conductivity, insufficient mechanical puncture resistance, and poor cycling stability at high current densities, this invention provides a silicone rubber-based composite electrolyte, its preparation method, and its applications. The electrolyte utilizes ion-doped hydroxyapatite nanowires to construct a continuous inorganic lithium-conducting network, and graft-modified silicone rubber provides flexibility, elasticity, and adaptive electrode interface capabilities, achieving synergy between the organic flexible phase and the inorganic reinforcing phase.

[0006] The first aspect of the present invention provides a silicone rubber-based composite electrolyte, the electrolyte comprising silicone rubber, modified small molecules, photoinitiator, crosslinking agent, ion-doped hydroxyapatite, and lithium salt; wherein the ion-doped hydroxyapatite is dispersed in the modified silicone rubber in the form of nanowires and / or fiber networks formed by overlapping nanowires. Based on the weight of silicone rubber, the content of modified small molecules is 25 wt% to 60 wt%, the content of photoinitiator is 0.1 wt% to 1 wt%, the content of crosslinking agent is 0.3 wt% to 3 wt%, the content of doped hydroxyapatite is 10 wt% to 50 wt%, and the content of lithium salt is 8 wt% to 30 wt%.

[0007] In one particular scheme, based on the weight of silicone rubber, the content of modified small molecules is 25 wt% to 60 wt%, the content of photoinitiator is 0.1 wt% to 1 wt%, the content of crosslinking agent is 0.3 wt% to 3 wt%, the content of doped hydroxyapatite is 20 wt% to 30 wt%, and the content of lithium salt is 8 wt% to 30 wt%.

[0008] Furthermore, according to some specific embodiments of the present invention, the modified silicone rubber is a silicone rubber comprising one or more polar functional groups selected from ester, ether, cyano, sulfone and fluoroaryl groups.

[0009] Preferably, the silicone rubber is selected from one or more of hydrogen-containing silicone rubber, hydroxyl-terminated silicone rubber, amino silicone rubber, epoxy silicone rubber, mercapto silicone rubber, chloropropyl silicone rubber, phenyl silicone rubber, ester silicone rubber, and vinyl silicone rubber.

[0010] Furthermore, in the silicone rubber-based composite electrolyte, the modifying groups in the modified small molecules are selected from one or more of ester groups, ether groups, cyano groups, sulfone groups, and fluoroaryl groups, preferably thiol groups.

[0011] Furthermore, in the silicone rubber-based composite electrolyte, the modified small molecule is selected from one or more of the following: methyl mercaptoacetate, ethyl mercaptoacetate, butyl mercaptoacetate, methyl 3-mercaptopropionate, ethyl 3-mercaptopropionate, butyl 3-mercaptopropionate, 2-methoxyethanethiol, 2-ethoxyethanethiol, 2-(2-methoxyethoxy)ethanethiol, mercaptopolyethylene glycol monomethyl ether, 3-mercaptopropionitrile, 2-mercaptoacetonitrile, acrylonitrile, vinyl sulfone, divinyl sulfone, 4-fluorostyrene, and 3-fluorostyrene.

[0012] Furthermore, in the silicone rubber-based composite electrolyte, the modified small molecule is selected from one or more of 3-mercaptopropionate butyl ester, ethyl mercaptoacetate, methyl mercaptopropionate, ethyl mercaptopropionate, and isooctyl mercaptopropionate.

[0013] Furthermore, in the silicone rubber-based composite electrolyte, the photoinitiator must have the property of polymerization under ultraviolet light irradiation, and is preferably selected from one or more of 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methylacetophenone, benzoin dimethyl ether, and azobisisobutyronitrile.

[0014] Furthermore, in the silicone rubber-based composite electrolyte, the modified silicone rubber is a modified silicone rubber formed by the click reaction of the modified small molecule, the crosslinking agent, and the silicone rubber. The crosslinking agent is preferably a mercapto crosslinking agent, and is more preferably selected from one or more of 1,2-ethylenedithiol, 1,3-propanedithiol, 1,4-butanedithiol, trimethylolpropane tris(3-mercaptopropionate), and pentaerythritol tetra(3-mercaptopropionate).

[0015] Furthermore, in the silicone rubber-based composite electrolyte, the hydroxyapatite basic composition of the doped ions includes Ca, P, and O elements, and includes one or more of lithium ions, sodium ions, potassium ions, magnesium ions, and zinc ions, with the doped ions at least partially replacing the Ca in the hydroxyapatite lattice. 2+ At the site, the hydroxyapatite doped with the ions retains the hydroxyapatite crystal structure.

[0016] Furthermore, in the aforementioned silicone rubber-based composite electrolyte, the lithium salt is one or more of inorganic lithium salts and / or organic lithium salts; the inorganic lithium salt is selected from one or more of lithium nitrate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, and lithium hexafluorophosphate; the organic lithium salt is selected from one or more of lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide, preferably one or more of lithium nitrate and lithium bis(trifluoromethanesulfonyl)imide.

[0017] Furthermore, in the aforementioned silicone rubber-based composite electrolyte, the length of the doped hydroxyapatite nanowires is 1 μm to 200 μm, and the diameter is 5 nm to 500 nm; the thickness of the fiber membrane formed by the nanowires is 20 μm to 150 μm.

[0018] Furthermore, in the aforementioned silicone rubber-based composite electrolyte, the thickness of the silicone rubber-based composite electrolyte is 30μm to 200μm.

[0019] Furthermore, the room temperature ionic conductivity of the aforementioned silicone rubber-based composite electrolyte is 5 × 10⁻⁶. -5 ~5×10 -4 S / cm.

[0020] Furthermore, the electrochemical stability window of the silicone rubber-based composite electrolyte is not less than 5.0V.

[0021] Furthermore, the puncture resistance of the silicone rubber-based composite electrolyte is not less than 0.2 N / mm.

[0022] A second aspect of this invention provides a method for preparing a silicone rubber-based composite electrolyte, the method comprising the following steps: (1) Preparation of modified silicone rubber precursor solution; (2) Preparation of ion-doped hydroxyapatite; (3) In a solvent, the modified silicone rubber precursor solution obtained in step (1) is combined with the hydroxyapatite fiber membrane doped with ions obtained in step (2), and then cured and dried to obtain a silicone rubber-based composite electrolyte.

[0023] Furthermore, according to some specific embodiments of the present invention, the modified silicone rubber precursor solution prepared in step (1) is selected from any one of the following precursor solutions: (1.1) Silicone rubber containing different modified groups, photoinitiator, crosslinking agent and lithium salt are mixed to obtain modified silicone rubber precursor solution; (1.2) Vinyl silicone rubber, modified small molecules, photoinitiator, crosslinking agent and lithium salt are mixed to obtain modified silicone rubber precursor solution.

[0024] Furthermore, according to some specific embodiments of the present invention, in step (1.1), the silicone rubber containing different modified groups is selected from one or more of hydrogen-containing silicone rubber, hydroxyl-terminated silicone rubber, amino silicone rubber, epoxy-based silicone rubber, mercapto silicone rubber, chloropropyl silicone rubber, phenyl silicone rubber, ester-based silicone rubber and vinyl silicone rubber.

[0025] Furthermore, according to some specific embodiments of the present invention, when the silicone rubber in step (1.1) is vinyl silicone rubber, the modified silicone rubber precursor solution prepared in step (1) is preferably prepared in the manner described in (1.2).

[0026] Furthermore, according to some specific embodiments of the present invention, in step (1.2), the modified small molecule is selected from one or more of methyl mercaptoacetate, ethyl mercaptoacetate, butyl mercaptoacetate, methyl 3-mercaptopropionate, ethyl 3-mercaptopropionate, butyl 3-mercaptopropionate, 2-methoxyethanethiol, 2-ethoxyethanethiol, 2-(2-methoxyethoxy)ethanethiol, mercaptopolyethylene glycol monomethyl ether, 3-mercaptopropionitrile, 2-mercaptoacetonitrile, acrylonitrile, vinyl sulfone, divinyl sulfone, 4-fluorostyrene, and 3-fluorostyrene.

[0027] Furthermore, according to some specific embodiments of the present invention, the photoinitiators in steps (1.1) and (1.2) must have the property of polymerization under ultraviolet light irradiation, and are each independently selected from one or more of 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methylacetone, benzoin dimethyl ether, and azobisisobutyronitrile.

[0028] Furthermore, according to some specific embodiments of the present invention, the crosslinked structure synthesized by the click reaction of silicone rubber under ultraviolet light in step (1) is formed by the reaction of a mercapto-containing crosslinking agent with silicone rubber, wherein the mercapto-containing crosslinking agent can be selected from one or more of 1,2-ethanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, trimethylolpropane tris(3-mercaptopropionate), and pentaerythritol tetra(3-mercaptopropionate).

[0029] Furthermore, according to some specific embodiments of the present invention, in steps (1.1) and (1.2), each lithium salt is independently one or more of inorganic lithium salt and / or organic lithium salt; each inorganic lithium salt is independently selected from one or more of lithium nitrate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, and lithium hexafluorophosphate; each organic lithium salt is independently selected from one or more of lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide, preferably one or two of lithium bis(difluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

[0030] Furthermore, according to some specific embodiments of the present invention, wherein, based on 100 parts by mass of silicone rubber, the amounts of the modified small molecule, lithium salt, photoinitiator and crosslinking agent are 10-80 parts by mass, 10-30 parts by mass, 0.05-5 parts by mass and 0.05-10 parts by mass, respectively.

[0031] Furthermore, according to some specific embodiments of the present invention, the preparation temperature of the precursor solution is 25-80°C, and the pre-reaction time is 2-16 h; preferably, the precursor solution is prepared under the condition of stirring at 60°C for 8 h.

[0032] Furthermore, according to some specific embodiments of the present invention, the method for preparing doped hydroxyapatite in step (2) includes one of the following preparation methods: (2.1) The doped ion salt was mixed with fibrous hydroxyapatite for ion exchange, washed with water, washed with alcohol, dried, and then the membrane was drawn to obtain a hydroxyapatite fiber membrane with doped ions. (2.2) The calcium source, phosphorus source, doped ion salt and alkaline regulator are mixed in the aqueous phase, the pH is adjusted to 9-12 and then hydrothermal reaction is carried out. The mixture is washed with water, washed with alcohol, dried and drawn to obtain ion-doped hydroxyapatite fiber membrane.

[0033] Furthermore, according to some specific embodiments of the present invention, in step (2.1), the hydroxyapatite suspension is washed with alcohol and then with water to obtain a hydroxyapatite suspension with doped ions removed from impurities.

[0034] Furthermore, according to some specific embodiments of the present invention, in step (2.1), a hydroxyapatite suspension with doped ions at a concentration of 0.1 to 10 mg / mL is subjected to vacuum filtration and dried at 60 to 100°C for 6 to 24 hours to obtain a lithium-doped hydroxyapatite fiber membrane.

[0035] Furthermore, according to some specific embodiments of the present invention, in step (2.2), the calcium source is selected from one or more of calcium chloride, calcium nitrate, and calcium acetate.

[0036] Furthermore, according to some specific embodiments of the present invention, in step (2.2), the phosphorus source is selected from one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, and ammonium phosphate.

[0037] Furthermore, according to some specific embodiments of the present invention, in step (2.2), the pH adjustment is performed using a pH modifier, preferably the pH modifier is selected from one or more of sodium hydroxide, potassium hydroxide, and ammonia water.

[0038] Furthermore, according to some specific embodiments of the present invention, in step (2.2), the hydrothermal reaction can be a conventional hydrothermal reaction or a microwave hydrothermal reaction; preferably a microwave hydrothermal reaction, under which the reaction temperature is 160-220°C and the reaction time is 1-8h to obtain a hydroxyapatite suspension, preferably at 180-200°C for 4-6h.

[0039] Furthermore, according to some specific embodiments of the present invention, in steps (2.1) and (2.2), the doped ionic salts are each independently selected from one or more of zinc salts, lithium salts, sodium salts, magnesium salts and potassium salts; preferably, they are metal ions consistent with the battery; wherein, the lithium salt is selected from one or more of lithium nitrate, lithium chloride, lithium acetate and lithium hydroxide; preferably, it is lithium nitrate.

[0040] Furthermore, according to some specific embodiments of the present invention, in step (3), the solvent is selected from one or more of tetrahydrofuran, acetonitrile, dichloromethane, toluene and xylene; preferably tetrahydrofuran.

[0041] Furthermore, according to some specific embodiments of the present invention, in step (3), the curing is performed by curing under 40-100 watts of ultraviolet light for 1-10 minutes; preferably, the curing is performed by curing under 60 watts of ultraviolet light for 3-5 minutes.

[0042] Furthermore, according to some specific embodiments of the present invention, in step (3), the drying conditions are vacuum drying, wherein the drying temperature is 50-100°C and the drying time is 3-24h; preferably, the drying conditions are drying at 80°C for 6-8h or drying at 60°C for 12-16h.

[0043] The third aspect of this invention provides a silicone rubber-based composite electrolyte prepared by the preparation method described in the second aspect.

[0044] The fourth aspect of the present invention provides the application of the silicone rubber-based composite electrolyte as described in the first or third aspect in a solid-state battery.

[0045] Preferably, the solid-state battery is a lithium metal solid-state battery, a solid-state lithium-ion battery, a flexible solid-state battery, or a solid-state pouch battery.

[0046] The fifth aspect of the present invention provides a solid-state battery, comprising a positive electrode, a lithium metal negative electrode, and a solid electrolyte located between the positive electrode and the negative electrode, wherein the solid electrolyte is a silicone rubber-based composite electrolyte as described in the first or third aspect.

[0047] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The present invention introduces polar functional groups into the silicone rubber chain segment through mercapto-olefin click reaction, thereby improving the dissociation of lithium salt and the conduction of lithium ions by silicone rubber, while maintaining the high elasticity and good interfacial adhesion of silicone rubber.

[0048] (2) The present invention uses ion-doped hydroxyapatite nanowires to construct an inorganic fiber network, which can provide a continuous lithium conduction path and improve the electrolyte's resistance to puncture, thereby helping to suppress lithium dendrite puncture and reduce interface impedance.

[0049] (3) The silicone rubber-based composite electrolyte of the present invention has high ionic conductivity, wide electrochemical stability window, excellent flexibility and good thermal stability, and has application potential in lithium metal solid-state batteries, flexible batteries and pouch batteries. Attached Figure Description

[0050] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0051] Figure 1 This is a nanoindentation test image of the silicone rubber-based composite electrolyte prepared in Example 1 of the present invention.

[0052] Figure 2 The image (a) shows the actual silicone rubber-based composite electrolyte prepared in Example 1 of this invention.

[0053] Figure 3 The images shown are scanning electron microscope images of the silicone rubber-based composite electrolyte prepared in Example 1 of this invention, where (b) is a cross-sectional morphology image and (c) is a surface morphology image, with a scale bar of 100 μm.

[0054] Figure 4 This is a test diagram of the electrochemical stability window of the silicone rubber-based composite electrolyte prepared in Example 1 of the present invention.

[0055] Figure 5 The diagram shows the constant current charge-discharge cycle of a lithium symmetric battery assembled using the silicone rubber-based composite electrolyte prepared in Example 1 of this invention.

[0056] Figure 6 The graph shows the cycle performance of a lithium iron phosphate full battery assembled using the silicone rubber-based composite electrolyte prepared in Example 1 of this invention.

[0057] In the accompanying drawings, Li-HA / SC (or SR-HA-Li) represents the composite electrolyte formed by the doped ion hydroxyapatite and silicone rubber prepared in Example 1, and SRCOO represents the grafted ester-based silicone rubber electrolyte prepared in Comparative Example 2. Detailed Implementation

[0058] The following embodiments are provided to better understand the present invention and are not intended to limit the scope of the invention, nor do they constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention obtained by any person under the guidance of the present invention or by combining the present invention with prior art features falls within the scope of protection of the present invention.

[0059] The present invention will now be described in detail with reference to the embodiments and accompanying drawings, but the scope of protection of the present invention is not limited to the embodiments.

[0060] Unless otherwise stated, the word "comprising" in this specification and claims should be understood in an open-ended sense and does not exclude other components, steps, or conditions. The numerical range of parameters herein includes endpoint values ​​and any intermediate values ​​between endpoints.

[0061] In this document, for ease of description, spatial relative terms such as “below,” “under,” “down,” “above,” “above,” “up,” etc., are used to describe the relationship of one element or feature to another element or feature in the accompanying drawings. It should be understood that spatial relative terms are intended to encompass different orientations of an object in use or operation, in addition to those depicted in the figures. For example, if an object in the figure is flipped, an element described as “below” or “under” another element or feature would be oriented “above” that element or feature. Thus, the exemplary term “below” can encompass both the downward and upward orientations. An object may also have other orientations (rotated 90 degrees or other orientations), and the spatial relative terms used herein should be interpreted accordingly.

[0062] In this document, the terms "first," "second," etc., are used to distinguish two different elements or parts, and are not used to define specific positions or relative relationships. In other words, in some embodiments, the terms "first," "second," etc., can also be used interchangeably.

[0063] In this document, all numeric values ​​of parameters (e.g., quantity or condition) should be understood to be modified by the term “about” in all cases, regardless of whether “about” actually appears before the numeric value.

[0064] In this document, unless specific experimental steps or conditions are specified in the examples and comparative examples, they can be performed according to the conventional experimental procedures or conditions described in the literature in this field. Reagents or instruments used without specified manufacturers are all commercially available conventional reagent products.

[0065] Example 1 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of vinyl silicone rubber and place it in a sample bottle. Add 0.08g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1.5g of butyl 3-mercaptopropionate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 30μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0066] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10, followed by the addition of 0.111 g of LiNO3 and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and subjected to hydrothermal reaction at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The silicone rubber electrolyte precursor solution was diluted with tetrahydrofuran and stirred evenly at room temperature and 250 rpm. Then it was dropped into the hydroxyapatite fiber membrane and allowed to stand for 12 h to fully wet the fiber network. Subsequently, it was cured by ultraviolet light for 3 min and vacuum dried at 60°C for 12 h to obtain the silicone rubber-based composite electrolyte.

[0067] Nanoindentation testing was performed on the composite electrolyte. The sample was fixed on the test stage, and a nanoindenter was used to vertically press the indenter into the sample, continuously recording the load-indentation depth curve. Figure 1 As shown, when the maximum indentation depth is 3000 nm, the maximum load of the composite electrolyte in Example 1 is approximately 25 μN. Its morphology was characterized. Figure 2 A physical image of the silicone rubber-based composite electrolyte (a); Figure 3 (b) and (c) are its cross-sectional and surface morphology diagrams, respectively, both at a scale of 100 μm. Figure 2 and Figure 3 As can be seen, Example 1 yielded a silicone rubber-based composite electrolyte membrane with a continuous surface and uniform cross-sectional thickness.

[0068] Example 2 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of vinyl silicone rubber and place it in a sample bottle. Add 0.1g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 0.5g of butyl 3-mercaptopropionate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 30μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0069] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10, followed by the addition of 0.111 g of LiNO3 and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and subjected to hydrothermal reaction at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The silicone rubber electrolyte precursor solution was diluted with tetrahydrofuran and stirred evenly at room temperature and 250 rpm. Then it was dropped into the hydroxyapatite fiber membrane and allowed to stand for 12 h to fully wet the fiber network. Subsequently, it was cured by ultraviolet light for 3 min and vacuum dried at 60°C for 12 h to obtain the silicone rubber-based composite electrolyte.

[0070] Example 3 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of vinyl silicone rubber and place it in a sample bottle. Add 0.08g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1.5g of butyl 3-mercaptopropionate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 30μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0071] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10, followed by the addition of 0.111 g of LiNO3 and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and subjected to hydrothermal reaction at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. Silicone rubber electrolyte was dropped into a hydroxyapatite fiber membrane and allowed to stand for 12 hours to allow the precursor solution to fully wet the fiber network. Subsequently, it was irradiated with ultraviolet light for 3 minutes to cure it and then vacuum dried at 60°C for 12 hours to obtain a silicone rubber-based composite electrolyte.

[0072] Example 4 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of vinyl silicone rubber and place it in a sample bottle. Add 0.08g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1.5g of butyl 3-mercaptopropionate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 30μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0073] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 9, followed by the addition of 0.111 g of LiNO3 and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and hydrothermally reacted at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. Silicone rubber precursor solution was dropped into hydroxyapatite fiber membrane and allowed to stand for 12 hours to fully wet the fiber network; then it was cured by ultraviolet light for 3 minutes and vacuum dried at 60°C for 12 hours to obtain silicone rubber-based composite electrolyte.

[0074] Example 5 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of vinyl silicone rubber and place it in a sample bottle. Add 0.1g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1.2g of butyl 3-mercaptopropionate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 20μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0075] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10, followed by the addition of 0.111 g of LiNO3 and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and subjected to hydrothermal reaction at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The silicone rubber electrolyte precursor solution was diluted with tetrahydrofuran and stirred evenly at room temperature and 250 rpm. Then it was dropped into the hydroxyapatite fiber membrane and allowed to stand for 12 h to fully wet the fiber network. Subsequently, it was cured by ultraviolet light for 3 min and vacuum dried at 60°C for 12 h to obtain the silicone rubber-based composite electrolyte.

[0076] Example 6 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of vinyl silicone rubber and place it in a sample bottle. Add 0.08g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1.5g of butyl 3-mercaptopropionate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 30μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0077] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and then mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10. 0.111 g of ZnSO4 was then added and stirred until completely dissolved. The resulting solution was transferred to a microwave reactor and hydrothermally reacted at 200°C for 6 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, obtaining a hydroxyapatite suspension. The hydroxyapatite suspension at 1 mg / mL was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The silicone rubber electrolyte precursor solution was diluted with tetrahydrofuran and stirred evenly at room temperature and 250 rpm. Then it was dropped into the hydroxyapatite fiber membrane and allowed to stand for 12 h to fully wet the fiber network. Subsequently, it was cured by ultraviolet light for 3 min and vacuum dried at 60°C for 12 h to obtain the silicone rubber-based composite electrolyte.

[0078] Example 7 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of vinyl silicone rubber and place it in a sample bottle. Add 0.08g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1.5g of butyl 3-mercaptopropionate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 30μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0079] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10, followed by the addition of 0.111 g of NaCl and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and subjected to hydrothermal reaction at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The silicone rubber electrolyte precursor solution was diluted with tetrahydrofuran and stirred evenly at room temperature and 250 rpm. Then it was dropped into the hydroxyapatite fiber membrane and allowed to stand for 12 h to fully wet the fiber network. Subsequently, it was cured by ultraviolet light for 3 min and vacuum dried at 60°C for 12 h to obtain the silicone rubber-based composite electrolyte.

[0080] Example 8 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of mercaptosilicone rubber and place it in a sample bottle. Add 0.1g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1g of methacrylate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 20μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0081] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10, followed by the addition of 0.111 g of LiNO3 and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and subjected to hydrothermal reaction at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The silicone rubber electrolyte precursor solution was diluted with tetrahydrofuran and stirred evenly at room temperature and 250 rpm. Then it was dropped into the hydroxyapatite fiber membrane and allowed to stand for 12 h to fully wet the fiber network. Subsequently, it was cured by ultraviolet light for 3 min and vacuum dried at 60°C for 12 h to obtain the silicone rubber-based composite electrolyte.

[0082] Example 9 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of mercaptosilicone rubber and place it in a sample bottle. Add 0.1g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 0.5g of 4-fluorostyrene. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 20μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0083] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10, followed by the addition of 0.111 g of LiNO3 and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and subjected to hydrothermal reaction at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The silicone rubber electrolyte precursor solution was diluted with tetrahydrofuran and stirred evenly at room temperature and 250 rpm. Then it was dropped into the hydroxyapatite fiber membrane and allowed to stand for 12 h to fully wet the fiber network. Subsequently, it was cured by ultraviolet light for 3 min and vacuum dried at 60°C for 12 h to obtain the silicone rubber-based composite electrolyte.

[0084] Comparative Example 1 Preparation of silicone rubber electrolyte precursor solution: 3g of vinyl silicone rubber was weighed and placed in a sample bottle. 0.08g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1.5g of butyl 3-mercaptopropionate were added. The mixture was heated and stirred at 60°C and 300rpm for 8h. Then, 0.9g of lithium bis(trifluoromethanesulfonyl)imide was added in a glove box and stirred at 60°C and 300rpm until the lithium salt was completely dissolved. Subsequently, 30μL of 1,2-ethylenedithiol was added, and the mixture was stirred evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution. The solution was then cured by UV irradiation for 3min and vacuum dried at 60°C for 12h to obtain the silicone rubber-based electrolyte.

[0085] Comparative Example 2 Preparation of silicone rubber electrolyte precursor solution: Weigh 3g of vinyl silicone rubber and place it in a sample bottle. Add 0.08g of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) and 1.5g of butyl 3-mercaptopropionate. Heat and stir at 60°C and 300rpm for 8h. Then add 0.9g of lithium bis(trifluoromethanesulfonyl)imide in a glove box and stir at 60°C and 300rpm until the lithium salt is completely dissolved. Then add 30μL of 1,2-ethylenedithiol and stir evenly at room temperature and 300rpm to obtain the modified silicone rubber precursor solution.

[0086] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and then mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10. The resulting solution was transferred to a microwave reactor and hydrothermally reacted at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, and then 150 mL of deionized water was added and stirred to disperse, obtaining a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The silicone rubber electrolyte precursor solution was diluted with tetrahydrofuran and stirred evenly at room temperature and 250 rpm. Then it was dropped into the hydroxyapatite fiber membrane and allowed to stand for 12 h to fully wet the fiber network. Subsequently, it was cured by ultraviolet light for 3 min and vacuum dried at 60°C for 12 h to obtain the silicone rubber-based composite electrolyte.

[0087] Comparative Example 3 Weigh 0.5 g of PEO and place it in 10 mL of ultra-dry acetonitrile. Then, place the mixture in an environment set to 60 °C and heat and stir at 300 rpm until the PEO is completely dissolved, forming a homogeneous solution. After the solution is prepared, transfer it to a glove box and add 0.33 g of LiTFSI to the solution. Stir continuously at 500 rpm at room temperature until the LiTFSI is fully dissolved. Pour the solution onto a polytetrafluoroethylene (PTFE) plate, allow it to stand to ensure uniform flow, and let it stand at room temperature for 12 h. Then, transfer it to an oven to dry, obtaining the PEO solid electrolyte (PEO).

[0088] Comparative Example 4 Weigh 0.5 g of PEO and place it in 10 mL of ultra-dry acetonitrile. Then, place the mixture in an environment set to 60 °C and heat and stir at 300 rpm until the PEO is completely dissolved, forming a homogeneous solution. After the solution is prepared, transfer it to a glove box and add 0.33 g of LiTFSI to the solution. Stir continuously at 500 rpm at room temperature until the LiTFSI is fully dissolved. Pour the solution onto a polytetrafluoroethylene (PTFE) plate, allow it to stand to ensure uniform flow, and let it stand at room temperature for 12 h. Then, transfer it to an oven to dry, obtaining the PEO solid electrolyte (PEO).

[0089] 4.8 g of sodium oleate and 0.333 g of anhydrous calcium chloride were weighed and dissolved in deionized water, stirred until completely dissolved, and mixed thoroughly. Separately, 0.56 g of anhydrous sodium dihydrogen phosphate was weighed and dissolved in deionized water, then slowly added dropwise to the above mixed solution. NaOH solution was then added dropwise to adjust the pH to 10, followed by the addition of 0.111 g of LiNO3 and stirring until completely dissolved. The resulting solution was transferred to a microwave reactor and subjected to hydrothermal reaction at 200°C for 4 hours. After natural cooling, a product solution containing hydroxyapatite was obtained. The product was washed three times with alcohol and three times with water, then 150 mL of deionized water was added and stirred to disperse, yielding a lithium-doped hydroxyapatite suspension. This 1 mg / mL hydroxyapatite suspension was then vacuum filtered. The resulting solid product was dried at 80°C for 12 hours to obtain a hydroxyapatite fiber membrane of uniform thickness. The above solution was poured into a hydroxyapatite fiber membrane and left to stand for 12 hours to allow the precursor solution to fully wet the fiber network; then it was transferred to an oven to dry to obtain the PEO-based composite electrolyte.

[0090] Evaluation Test Thickness test: The thickness of the electrolyte membrane at 5 different locations was measured at room temperature using a digital micrometer, and the arithmetic mean was taken as the sample thickness.

[0091] Ionic conductivity test: The electrolyte sheet is clamped between two stainless steel blocking electrodes to assemble a stainless steel|electrolyte|stainless steel simulated battery; AC impedance test is performed at 25°C with 10 mV AC disturbance and a frequency range of 1 MHz to 0.1 Hz. The body resistance R is obtained from the intersection of the high-frequency region and the real axis. The ionic conductivity is calculated according to σ=L / (R×S), where L is the thickness of the electrolyte sheet and S is the effective contact area between the electrode and the electrolyte sheet.

[0092] Puncture strength test: The puncture strength test is carried out by an electronic universal testing machine. The electrolyte membrane is flattened and clamped on the sample holder. A cylindrical probe with a diameter of 1 mm is used to puncture the sample vertically at a speed of 10 mm / min. The maximum load F before the sample is penetrated is recorded. The puncture strength is calculated as F / L, where L is the sample thickness. Three parallel samples are tested in each group and the average value is taken.

[0093] Electrochemical stability window test: Assemble a stainless steel|electrolyte|lithium metal battery and perform linear scan voltammetry at 25°C with a scan rate of 1 mV / s from 2.0 V to 6.0 V (vs. Li / Li+). The potential at which the oxidation current increases significantly is taken as the upper limit of the electrochemical stability window.

[0094] Lithium-symmetric battery testing: Assemble lithium|electrolyte|lithium-symmetric batteries and perform constant current cycling at 30°C with a current density of 0.1 mA·cm⁻² and a single deposition / stripping areal capacity of 0.1 mAh·cm⁻². Record voltage-time curves and stable cycling time.

[0095] Full cell cycle test: A full cell was assembled with lithium metal as the negative electrode, lithium iron phosphate as the positive electrode, and solid electrolyte as the test electrolyte. The cell was subjected to constant current charge-discharge cycle at 0.2C rate at 30°C, and the changes in specific capacity and coulombic efficiency with the number of cycles were recorded.

[0096] Test results are available Figure 4 , Figure 5 and Figure 6 , and Table 1.

[0097] Table 1. Test data of the elastic electrolytes prepared in Examples 1-9 and Comparative Examples 1-4.

[0098] Ionic conductivity was determined using an AC impedance spectroscopy method. A solid electrolyte sheet was sandwiched between two stainless steel sheets, and the impedance was measured at room temperature. The ionic conductivity was calculated using σ = L / (R × S), where L is the thickness of the electrolyte sheet, R is the impedance of the electrolyte sheet, and S is the effective contact area. The room temperature ionic conductivity of the silicone rubber-based composite solid electrolyte obtained in Example 1 reached 2.02 × 10⁻⁶. -4 S / cm.

[0099] Puncture strength was characterized by puncture testing. The puncture strength of the silicone rubber-based composite solid electrolyte obtained in Example 1 reached 0.6 N / mm, indicating that the hydroxyapatite fiber network can significantly improve the mechanical puncture resistance of the silicone rubber electrolyte, which is beneficial for inhibiting lithium dendrite penetration through the electrolyte membrane.

[0100] The electrochemical stability window was determined by linear sweep voltammetry. The electrochemical stability window of the silicone rubber-based composite solid electrolyte obtained in Example 1 can be extended to 5.2V, demonstrating excellent high voltage stability.

[0101] The obtained electrolytes were used to assemble Li||Li symmetric cells, and the cells were tested at 30°C and 0.1 mA cm⁻¹. -2 Current density and 0.1 mAhcm -2 Cyclic testing was conducted under capacity conditions. The symmetric battery using the silicone rubber-based composite solid electrolyte of Example 1 could cycle stably for 2000 hours with minimal voltage fluctuations. An all-solid-state battery was assembled using a lithium metal anode, a lithium iron phosphate cathode, and a silicone rubber-based composite solid electrolyte. After 500 cycles at 30°C and 0.2C rate, the capacity retention rate still reached 77.3%, indicating that the electrolyte of this invention can balance ion transport, interface adhesion, and mechanical stability.

[0102] analyze: The above results demonstrate that lithium-doped hydroxyapatite forms a continuous inorganic fiber network within the silicone rubber matrix, promoting lithium salt dissociation and lithium-ion migration through lattice Li+ and surface active sites. Simultaneously, this fiber network enhances the puncture strength and thermal stability of the electrolyte membrane. The grafted ester-based silicone rubber matrix provides flexible segments and dynamic coordination sites, enabling the electrolyte to maintain close contact with the lithium metal anode and reducing interfacial impedance. Therefore, the silicone rubber-based composite electrolyte of this invention is suitable for high-safety, long-life lithium metal solid-state batteries.

[0103] Obviously, the above embodiments are merely illustrative examples to clearly illustrate the present invention and are not intended to limit the implementation. Those skilled in the art can make other variations or modifications based on the above description. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A silicone rubber-based composite electrolyte, the electrolyte comprising silicone rubber, modified small molecules, a photoinitiator, a crosslinking agent, ion-doped hydroxyapatite, and a lithium salt; wherein the ion-doped hydroxyapatite is dispersed in the modified silicone rubber in the form of nanowires and / or a fiber network formed by overlapping nanowires; Based on the weight of silicone rubber, the content of modified small molecules is 25 wt% to 60 wt%, the content of photoinitiator is 0.1 wt% to 1 wt%, the content of crosslinking agent is 0.3 wt% to 3 wt%, the content of doped hydroxyapatite is 10 wt% to 50 wt%, and the content of lithium salt is 8 wt% to 30 wt%.

2. The silicone rubber-based composite electrolyte according to claim 1, characterized in that, Based on the weight of silicone rubber, the content of modified small molecules is 25 wt%–60 wt%, the content of photoinitiator is 0.1 wt%–1 wt%, the content of crosslinking agent is 0.3 wt%–3 wt%, the content of doped hydroxyapatite is 20 wt%–30 wt%, and the content of lithium salt is 8 wt%–30 wt%. And / or, in the silicone rubber-based composite electrolyte, the modified silicone rubber is a modified silicone rubber containing one or more polar functional groups grafted with ester, ether, cyano, sulfone or fluoroaryl groups. Preferably, the silicone rubber is selected from one or more of hydrogen-containing silicone rubber, hydroxyl-terminated silicone rubber, amino silicone rubber, epoxy silicone rubber, mercapto silicone rubber, chloropropyl silicone rubber, phenyl silicone rubber, ester-based silicone rubber, and vinyl silicone rubber; More preferably, in the silicone rubber-based composite electrolyte, the modifying groups in the modified small molecule are selected from one or more of ester, ether, cyano, sulfone, and fluoroaryl groups; Preferably, the modified small molecule is selected from one or more of the following: methyl mercaptoacetate, ethyl mercaptoacetate, butyl mercaptoacetate, methyl 3-mercaptopropionate, ethyl 3-mercaptopropionate, butyl 3-mercaptopropionate, 2-methoxyethanethiol, 2-ethoxyethanethiol, 2-(2-methoxyethoxy)ethanethiol, mercaptopolyethylene glycol monomethyl ether, 3-mercaptopropionitrile, 2-mercaptoacetonitrile, acrylonitrile, vinyl sulfone, divinyl sulfone, 4-fluorostyrene, and 3-fluorostyrene. More preferably, the modifying group in the modified small molecule is a thiol group; More preferably, the modified small molecule is selected from one or more of 3-mercaptopropionate butyl ester, ethyl mercaptoacetate, methyl mercaptopropionate, ethyl mercaptopropionate and isooctyl mercaptopropionate; And / or, in the silicone rubber-based composite electrolyte, the photoinitiator is selected from one or more of 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methylacetophenone, dimethyl benzoate, and azobisisobutyronitrile; And / or, in the silicone rubber-based composite electrolyte, the modified silicone rubber is a modified silicone rubber formed by the click reaction of the modified small molecule, the crosslinking agent, and the silicone rubber. Preferably, the crosslinking agent is selected from one or more of 1,2-ethylenedithiol, 1,3-propanedithiol, 1,4-butanedithiol, trimethylolpropane tris(3-mercaptopropionate), and pentaerythritol tetra(3-mercaptopropionate). And / or, in the silicone rubber-based composite electrolyte, the hydroxyapatite basic composition of the doped ions includes Ca, P, and O elements, and includes one or more of lithium ions, sodium ions, potassium ions, magnesium ions, and zinc ions, and the doped ions at least partially replace Ca in the hydroxyapatite lattice. 2+ The hydroxyapatite with doped ions retains its hydroxyapatite crystal structure at the site. And / or, the lithium salt is one or more of inorganic lithium salts and / or organic lithium salts; the inorganic lithium salt is selected from one or more of lithium nitrate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, and lithium hexafluorophosphate; the organic lithium salt is selected from one or more of lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide, preferably one or two of lithium nitrate and lithium bis(trifluoromethanesulfonyl)imide.

3. The silicone rubber-based composite electrolyte according to claim 1 or 2, characterized in that, The thickness of the silicone rubber-based composite electrolyte is 30 μm to 200 μm; And / or, the room temperature ionic conductivity of the silicone rubber-based composite electrolyte is 5 × 10⁻⁶. -5 ~5×10 -4 S / cm; And / or, the electrochemical stability window of the silicone rubber-based composite electrolyte is not less than 5.0V; And / or, the puncture resistance of the silicone rubber-based composite electrolyte is not less than 0.2 N / mm.

4. A method for preparing a silicone rubber-based composite electrolyte as described in any one of claims 1-3, the method comprising the following steps: (1) Preparation of modified silicone rubber precursor solution; (2) Preparation of ion-doped hydroxyapatite; (3) In a solvent, the modified silicone rubber precursor solution obtained in step (1) is combined with the hydroxyapatite fiber membrane doped with ions obtained in step (2), and then cured and dried to obtain a silicone rubber-based composite electrolyte.

5. The preparation method according to claim 4, characterized in that, The modified silicone rubber precursor solution prepared in step (1) is selected from any one of the following precursor solutions: (1.1) Silicone rubber containing different modified groups, photoinitiator, crosslinking agent and lithium salt are mixed to obtain modified silicone rubber precursor solution; (1.2) Vinyl silicone rubber, modified small molecules, photoinitiator, crosslinking agent and lithium salt are mixed to obtain modified silicone rubber precursor solution; And / or, in step (1.1), the silicone rubber containing different modified groups is selected from one or more of the following: hydrogen-containing silicone rubber, hydroxyl-terminated silicone rubber, amino silicone rubber, epoxy-based silicone rubber, mercapto silicone rubber, chloropropyl silicone rubber, phenyl silicone rubber, ester-based silicone rubber, and vinyl silicone rubber. Wherein, when the silicone rubber in step (1.1) is vinyl silicone rubber, the modified silicone rubber precursor solution prepared in step (1) is preferably prepared in the manner described in (1.2); And / or, in step (1.2), the modified small molecule is selected from one or more of methyl mercaptoacetate, ethyl mercaptoacetate, butyl mercaptoacetate, methyl 3-mercaptopropionate, ethyl 3-mercaptopropionate, butyl 3-mercaptopropionate, 2-methoxyethanethiol, 2-ethoxyethanethiol, 2-(2-methoxyethoxy)ethanethiol, mercaptopolyethylene glycol monomethyl ether, 3-mercaptopropionitrile, 2-mercaptoacetonitrile, acrylonitrile, vinyl sulfone, divinyl sulfone, 4-fluorostyrene, and 3-fluorostyrene; Preferably, the photoinitiators in steps (1.1) and (1.2) must have the property of polymerization under ultraviolet light irradiation, and are each independently selected from one or more of 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methylacetophenone, benzoin dimethyl ether, and azobisisobutyronitrile; Preferably, in steps (1.1) and (1.2), each lithium salt is independently one or more of inorganic lithium salts and / or organic lithium salts; each inorganic lithium salt is independently selected from one or more of lithium nitrate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, and lithium hexafluorophosphate; each organic lithium salt is independently selected from one or more of lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide, and preferably one or two of lithium bis(difluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide. And / or, in step (1), the preparation temperature of the precursor solution is 25-80°C and the pre-reaction time is 2-16h; preferably, the precursor solution is prepared under the condition of stirring at 60°C for 8h.

6. The preparation method according to claim 4, characterized in that, The preparation method for preparing doped hydroxyapatite in step (2) includes one of the following preparation methods: (2.1) The doped ion salt was mixed with fibrous hydroxyapatite for ion exchange, washed with water, washed with alcohol, dried, and then the membrane was drawn to obtain a hydroxyapatite fiber membrane doped with ions. (2.2) Calcium source, phosphorus source, doped ion salt and alkaline regulator are mixed in aqueous phase, pH is adjusted to 9-12 and hydrothermal reaction is carried out, followed by water washing, alcohol washing, drying and membrane drawing to obtain ion-doped hydroxyapatite fiber membrane. Preferably, in step (2.2), the calcium source is selected from one or more of calcium chloride, calcium nitrate, and calcium acetate; Preferably, in step (2.2), the phosphorus source is selected from one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, and ammonium phosphate; Preferably, in step (2.2), the pH adjustment is performed using a pH modifier, and preferably the pH modifier is selected from one or more of sodium hydroxide, potassium hydroxide, and ammonia water; Preferably, in step (2.2), the hydrothermal reaction can be a conventional hydrothermal reaction or a microwave hydrothermal reaction; preferably, it is a microwave hydrothermal reaction, under which the reaction temperature is 160-220°C and the reaction time is 1-8h to obtain a hydroxyapatite suspension, preferably at 180-200°C for 4-6h. Preferably, in steps (2.1) and (2.2), the doped ionic salts are each independently selected from one or more of zinc salts, lithium salts, sodium salts, magnesium salts, and potassium salts; preferably, they are metal ions consistent with the battery; wherein, the lithium salt is selected from one or more of lithium nitrate, lithium chloride, lithium acetate, and lithium hydroxide; preferably, it is lithium nitrate.

7. The preparation method according to claim 4, characterized in that, In step (3), the solvent is selected from one or more of tetrahydrofuran, acetonitrile, dichloromethane, toluene, and xylene; The curing process involves curing under 40-100 watts of ultraviolet light for 1-10 minutes. The drying conditions are vacuum drying, wherein the drying temperature is 50–100°C and the drying time is 3–24 hours; Preferably, the solvent is tetrahydrofuran; Preferably, the curing is performed by irradiating with 60 watts of ultraviolet light for 3-5 minutes; Preferably, the drying conditions are drying at 80°C for 6-8 hours or drying at 60°C for 12-16 hours.

8. A silicone rubber-based composite electrolyte prepared by the preparation method according to any one of claims 4-7.

9. The application of a silicone rubber-based composite electrolyte as described in any one of claims 1-3 and 8 in a solid-state battery; Preferably, the solid-state battery is a lithium metal solid-state battery, a solid-state lithium-ion battery, a flexible solid-state battery, or a solid-state pouch battery.

10. A solid-state battery, comprising a positive electrode, a lithium metal negative electrode, and a solid electrolyte located between the positive and negative electrodes, wherein, The solid electrolyte is a silicone rubber-based composite electrolyte as described in any one of claims 1-3 and 8.